The Adoption of Runosong Techniques in Estonian Antiphonal Psalmody: Toward a Circular Model of Chanting - Jõks Eerik (Journal of Ethnology and Folkloristics)
This interdisciplinary hymnological article reflects on some aspects of a creative journey within the evolutionary process of Estonian-language antiphonal psalm-ody from 2010 to 2024. It investigates the integration of performance elements from the archaic communal folk singing tradition of Estonian runosong (regilaul) into the contemporary prose-rhythm Estonian ecclesiastical chant, or pühalaul (‘sacred chant’), with a particular focus on antiphonal psalmody. Employing an artistic research approach, intertwined with autoethnography, the study draws on long-term artistic experimentation with pühalaul to explore how this idiomatic style for communal chanting in the Estonian language came into being. This research addresses a long-standing challenge in Estonian hymnology: the need to create an idiomatic ecclesiastical chanting practice aligned with the prosodic qualities of Estonian prose texts and local communal singing traditions, rather than relying on musical models and traditions, including rhythmic patterns shaped by German and other Indo-European languages, which were introduced through historical contact and adopted over time. While the broader repertoire and melodic foundations of Estonian antiphonal psalmody were shaped during earlier stages of the artistic research process, the present focus is on elaborating specific performance techniques for chanting, to achieve a runosong-like uninterrupted flow. Drawing on selected features of runosong, such as the circular musical phrase, anticipatory entry (leegajus), and ingressive phonation (inward speaking), the study culminates in the formulation of a circular model of antiphonal psalmody offering a new approach to communal ecclesiastical chanting.